MENGURAI KOMPLEKSITAS SATU PASANGAN CALON DALAM PEMILIHAN KEPALA DAERAH LANGSUNG - Nurdin, Reski Yanti (JPP (Jurnal Politik Profetik), 2017)
The existence of one pair of candidates who compete in direct elections is a new phenomenon in the procedural democracy in Indonesia. Various reasons that allow this phenomenon to occur range from a lack of decent and qualified political party cadres, reluctance of political parties to take possibly high risk due to the feedback provided by survey institutions, difficulties resulted from formal legislations for independent candidates and from several rules provided by the incumbents. This paper elaborates these problems and provides solutions to minimize the occurrence of one pair of candidates in the direct elections.